Lectin-like oxidized low-density lipoprotein receptor-1 promotes endothelial dysfunction in LDL receptor knockout background. (November 2017) - Hofmann, Anja; Brunssen, Coy; Poitz, David M.; Langbein, Heike; Strasser, Ruth H.; Henle, Thomas; Ravens, Ursula; Morawietz, Henning
Abstract: Objective: Lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) is the major receptor for oxidized LDL in endothelial cells. LOX-1 is highly expressed in atherosclerotic plaques. The impact of LOX-1 on development of endothelial dysfunction in large vessels in absence or presence of atherosclerosis-prone conditions has not been studied to date. Methods: Mice with endothelial cell-specific LOX-1 overexpression (bLOX-1tg) were analyzed. Wild-type (WT) mice served as controls. In addition, bLOX-1tg mice were crossed with LDL receptor knockout (Ldlr −/− ) mice. All mice were fed a western-type diet (WD) or control diet (CD) for 20 weeks. Afterwards, endothelial function was analyzed ex vivo in thoracic aortas using a Mulvany myograph. Results: WD induced hypertriglyceridemia (bLOX-1tg: 1.6-fold; WT: 1.4-fold) and hypercholesterolemia ( P  < 0.0001) in bLOX-1tg and WT mice without HDL-elevation in bLOX-1tg mice. Gonadal fat pad weight was 1.7 and 1.2-fold increased on CD and WD in bLOX-1tg mice compared to WT. LOX-1 overexpression impaired endothelial function by 15–16% ( P  < 0.05) on CD and WD. Crossing bLOX-1tg mice into Ldlr −/− background strongly elevated total (∼6-fold) and LDL-cholesterol (∼9-fold) compared to WT and bLOX-1tg mice on WD. Endothelial function in response to WD was impaired in bLOX-1tg/Ldlr −/− mice (Effmax : 56.7 ± 23.0%) compared to WT (Effmax : 88.2 ± 15.8%, P  < 0.001), bLOX-1tg (Effmax : 76.7 ± 12.9%, P  < 0.05) and Ldlr −/− mice (Effmax : 70.1 ± 13.1%, P  < 0.05). No differences between WT, bLOX-1tg and Ldlr −/− mice were detectable when comparing all genotypes. Conclusion: Endothelial LOX-1 overexpression in an atherosclerosis-prone background impairs endothelial function, proving its importance in the development of atherosclerosis.